Lesser trochanter fracture: the presenting feature of a more sinister pathology. (3rd June 2014) - Fox, Thomas Peter; Lakkol, Sandeshkumar; Oliver, Govind
Abstract : We report the rare case of a 75-year-old man who was hospitalised following referral by his general practitioner with a 4-day history of worsening groin pain. Initial radiographs demonstrated an isolated avulsion fracture of the lesser trochanter. There were associated bony changes indicating pathological bone disease, likely secondary to bony metastasis. Further investigation revealed a renal mass almost certainly consistent with a renal cell carcinoma. This case emphasises the importance of having a high index of suspicion for neoplastic pathology when low impact injuries result in fractures.